Dogs Do Not Show Pro-social Preferences towards Humans - Quervel-Chaumette, Mylène; Mainix, Gaëlle; Range, Friederike; Marshall-Pescini, Sarah (Frontiers in Psychology, 2016)
Pro-social behaviors are defined as voluntary actions that benefit others. Comparative studies have mostly focused on investigating the presence of pro-sociality across species in an intraspecific context. Taken together, results on both primates and non-primate species indicate that reliance on cooperation may be at work in the selection and maintenance of pro-social sentiments. Dogs appear to be the ideal model when investigating a species’ propensity for pro-sociality in an interspecific context because it has been suggested that as a consequence of domestication, they evolved an underlying temperament encouraging greater propensity to cooperate with human partners. In a recent study, using a food delivery paradigm, dogs were shown to preferentially express pro-social choices toward familiar compared to unfamiliar conspecifics. Using the same set-up and methods in the current study, we investigated dogs’ pro-social preferences toward familiar and unfamiliar human partners. We found that dogs’ pro-social tendencies did not extend to humans and the identity of the human partners did not influence the rate of food delivery. Interestingly, dogs tested with their human partners spent more time gazing at humans, and did so for longer after food consumption had ended than dogs tested with conspecific partners in the initial study. To allow comparability between results from dogs tested with a conspecific and a human partner, the latter were asked not to communicate with dogs in any way. However, this lack of communication from the human may have been aversive to dogs, leading them to cease performing the task earlier compared to the dogs paired with familiar conspecifics in the prior study. This is in line with previous findings suggesting that human communication in such contexts highly affects dogs’ responses. Consequently, we encourage further studies to examine dogs’ pro-social behavior toward humans taking into consideration their potential responses both with and without human communication.